1994
DOI: 10.1007/bf01211175
|View full text |Cite
|
Sign up to set email alerts
|

Source analysis of median nerve and finger stimulated somatosensory evoked potentials: Multichannel simultaneous recording of electric and magnetic fields combined with 3d-MR tomography

Abstract: At the current state of technology, multichannel simultaneous recording of combined electric potentials and magnetic fields should constitute the most powerful tool for separation and localization of focal brain activity. We performed an explorative study of multichannel simultaneous electric SEPs and magnetically recorded SEFs. MEG only sees tangentially oriented sources, while EEG signals include the entire activity of the brain. These characteristics were found to be very useful in separating multiple sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 36 publications
6
58
0
Order By: Relevance
“…In most of the somatosensory studies which we have performed (e.g., Elbert et al 1994Elbert et al ,1995, we do not obtain satisfying single ECD-fits at or after the peak of· the first major component (35-90 msec), but achieve excellent models during the upstroke of this component. This too would be in agreement with the assumption that S-II activation comes in only at stages beyond 50 msec, an assumption which is also consistent with the recent report by Buchner et al (1994) showing that early SEFs (N20-P20) and N30-P30 peaks) can be adequately modeled by a single EeD located close to the posterior bank of the central sulcus, in area 3b.…”
Section: Discussionsupporting
confidence: 79%
“…In most of the somatosensory studies which we have performed (e.g., Elbert et al 1994Elbert et al ,1995, we do not obtain satisfying single ECD-fits at or after the peak of· the first major component (35-90 msec), but achieve excellent models during the upstroke of this component. This too would be in agreement with the assumption that S-II activation comes in only at stages beyond 50 msec, an assumption which is also consistent with the recent report by Buchner et al (1994) showing that early SEFs (N20-P20) and N30-P30 peaks) can be adequately modeled by a single EeD located close to the posterior bank of the central sulcus, in area 3b.…”
Section: Discussionsupporting
confidence: 79%
“…Because there is no unique solution, it is necessary to apply constraints to the model, which may prove as powerful tool to localize sources without invasive measures. With respect to localization of median nerve SEP sources, dipole localization has been performed so far by using surface recordings only (Buchner et al 1994;Jung et al 2003Jung et al , 2008. We have successfully used this technique in an anatomically difficult region, the parasylvian cortex, to estimate the source of pain evoked potentials from subdural grid recordings (Vogel et al 2003), and the results were independently confirmed by another laboratory using depth recordings (Frot and Mauguière 2003).…”
Section: Introductionmentioning
confidence: 51%
“…4). Many investigations have been dedicated to the localizatioa of somatosensory-evoked fields (SEF) (28)(29)(30)(31)(32) (Fig. 4) reflecting the homuncular organization of the somatosensory cortex.…”
Section: Applications Of Msimentioning
confidence: 99%